ULTRASONOGRAFI UNTUK PREDIKSI LASERASI PARENKIM GINJAL DAN HEMATOMA PERIRENAL PADA PASIEN TRAUMA TUMPUL ABDOMEN DENGAN KECURIGAAN TRAUMA GINJAL - Richata, Galuh; Sugandi, Suwandi; Haroen, Zulhardi; E, Mumuh M; Noegroho, Bambang S; Tjahjodjati, Tjahjodjati; Safriadi, Ferry (Indonesian Journal of Urology, 2008)
Objective: To evaluate the sensitivity and the specificity of the ultrasound in predicting renal parenchyma laceration and perirenal hematoma in patients with abdominal blunt trauma with suspicion of renal trauma, as confirmed by operative findings in the explorative laparotomy. Material & methods: From March 2005 to March 2006, we found 28 patients admitted to the emergency department with abdominal blunt trauma with suspicion of renal trauma. Every patient was scanned sonografically to detect the presence of the renal parenchyma laceration and perirenal hematoma. All those patients underwent laparotomy for any certain indication, but not because of ultrasound findings. The ultrasound findings then were checked with the operative findings. Results: The sensitivity of the ultrasound in predicting renal parenchyma laceration is 53.8%, while its sensitivity in predicting perirenal hematoma is 75%. The specificity of ultrasound in predicting both renal parenchyma laceration and perirenal hematoma is 100%. Conclusion: Ultrasound for kidney trauma is sensitive in predicting the presence of perirenal hematoma, but not sensitive in predicting the presence of a renal parenchyma laceration. Ultrasound is very specific in predicting if both perirenal hematoma and renal parenchyma laceration are present.